Identification of Acoustic Indicators to Enable Certain Activities. The influence of sound on perception and social interaction in public spaces - Dohmen, Maud (My University, 2017)
Urban spaces are designed to facilitate certain activities. When designing the space, the sound environment is often not considered. However, sound may have an influence on the perception of the space and how a space is used. In this project the relationship between sound, perception and social behavior will be investigated. To do this, a series of sound measurements and questionnaires have been conducted in the center of Gothenburg, Sweden. With these data the relation between the soundscape and the use of a location is investigated. The relation between the various types of perception of a space (overall, visual and sound) has been analyzed. Based on the ratings for the quality of the overall area, visual aspects and sound aspects clusters can be seen of similar locations with the same quality ratings. The quality ratings have little relation to measurable acoustic indicators. However, they do display a relation with activity choice. To create a more complete view of what influences the perception and use of a space, a principle component analysis was made. From this three components can be found explaining 79% of the variance. The three components can be clustered under: tranquil green, socially active and sound level. Indicating that sound has an influence on the perception and use of a location. It is however, not the dominating one.
Keywords: Building Futures; Akustik; Building Futures; Acoustics